Clinical Case of a Patient with Small Bowel Obstruction and Multiple Diospirobesoaras of the Gastrointestinal Tract - A. S. Harutyunyan; V. D. Levitsky; V. V. Kiselev; P. A. Yartsev; A. V. Vodyasov; N. V. Shavrina (Неотложная медицинская помощь, 2020)
Abstract Small bowel obstruction (SBO) is 3-4% of all abdominal acute diseases. Small bowel obstruction due to bezoars is rare (2-4%), and is detected mainly in patients with predisposing risk factors: gastrointestinal motility disorders, psychiatric diseases, enzymatic insufficiency, previous bariatric surgery, diabetes mellitus and hypothyroidism complicated by gastroparesis. The leading role in the verification of small bowel obstruction in patients without surgical interventions on the abdominal organs should be given to computed tomography. According to the literature, the mortality from SBO due to bezoar may reach 30%. We present an unusual clinical case of recurrent small bowel obstruction with severe intestinal disease and septic shock induced by multiple phytobezoars and complicated with severe pseudomembranous colitis. Moreover, in our opinion, laparoscopic access can be used both for diagnostic and therapeutic purposes in patients with acute small bowel obstruction.